KOREKSI HERMENEUTIKA TERHADAP AYAT-AYAT QIWAMAH: STUDI ULUMUL QUR’AN DAN RELEVANSINYA DALAM RELASI SUAMI ISTRI MODERN - Mustianah, Siti (Bayani, 2025)
Classical interpretations of the qiw?mah verse (Q.S. an-Nis?’ [4]: 34) have often reinforced patriarchal gender relations by positioning men as absolute leaders within the household. This literal and ahistorical reading has contributed to the development of unequal family structures in many Muslim societies. This study aims to re-examine the concept of qiw?mah using a hermeneutical approach within the framework of ?ul?m al-Qur’?n, taking into account the higher objectives (maq??id al-shar?‘ah) of Islamic law, such as justice (?adl), compassion (ra?mah), and public welfare (ma?la?ah). Employing a qualitative library research method and critical analysis of both classical and contemporary exegesis, this study finds that qiw?mah should be understood not as unilateral legal authority, but as a moral responsibility grounded in mutual partnership. The findings indicate that a hermeneutical reinterpretation of gender-related verses is essential for building more just, dynamic, and contextually relevant Muslim family structures. This research contributes to the development of inclusive Qur’anic exegesis and serves as a scholarly and policy reference for reforming Islamic family law in line with contemporary understandings of gender justice and equality.